Novel pathway for corrinoid compounds production in lactobacillus - Torres, Andrea Carolina (2018)
Vitamin B12 or cobalamin is an essential metabolite for humans, which makes it an interesting compound for many research groups that focus in different producer-strains synthesis pathways. In this work, we report the influence of key intermediaries for cobalamin synthesis added to the culture medium in two Lactobacillus (L.) strains, L. reuteri CRL 1098 and L. coryniformis CRL 1001. Here, we report that addition of Co2+ and 5,6-dimethylbenzimidazole increased the corrinoid compounds production in both strains while addition of L-threonine increased only the corrinoid compounds production by CRL 1001 strain. Then, we purified and characterized by LC-MS the corrinoid compounds obtained. Physiological studies besides in silico analysis revealed that L. reuteri CRL 1098 and L. coryniformis CRL 1001 follow different pathways for the last steps of the corrinoid compounds synthesis.